Multisite reproducibility of quantitative susceptibility mapping and effective transverse relaxation rate in deep gray matter at 3 T using locally optimized sequences in 24 traveling heads. (1st July 2022) - Naji, Nashwan; Lauzon, M. Louis; Seres, Peter; Stolz, Emily; Frayne, Richard; Lebel, Catherine; Beaulieu, Christian; Wilman, Alan H.
Abstract : Iron concentration in the human brain plays a crucial role in several neurodegenerative diseases and can be monitored noninvasively using quantitative susceptibility mapping (QSM) and effective transverse relaxation rate (R2 *) mapping from multiecho T2 *‐weighted images. Large population studies enable better understanding of pathologies and can benefit from pooling multisite data. However, reproducibility may be compromised between sites and studies using different hardware and sequence protocols. This work investigates QSM and R2 * reproducibility at 3 T using locally optimized sequences from three centers and two vendors, and investigates possible reduction of cross‐site variability through postprocessing approaches. Twenty‐four healthy subjects traveled between three sites and were scanned twice at each site. Scan‐rescan measurements from seven deep gray matter regions were used for assessing within‐site and cross‐site reproducibility using intraclass correlation coefficient (ICC) and within‐subject standard deviation (SDw) measures. In addition, multiple QSM and R2 * postprocessing options were investigated with the aim to minimize cross‐site sequence‐related variations, including: mask generation approach, echo‐timing selection, harmonizing spatial resolution, field map estimation, susceptibility inversion method, and linear field correction for magnitude images. The same‐subject cross‐site region of interest measurements for QSM and R2 * were highly correlated (R 2  ≥ 0.94) and reproducible (mean ICC of 0.89 and 0.82 for QSM and R2 *, respectively). The mean cross‐site SDw was 4.16 parts per billion (ppb) for QSM and 1.27 s −1 for R2 *. For within‐site measurements of QSM and R2 *, the mean ICC was 0.97 and 0.87 and mean SDw was 2.36 ppb and 0.97 s −1, respectively. The precision level is regionally dependent and is reduced in the frontal lobe, near brain edges, and in white matter regions. Cross‐site QSM variability (mean SDw) was reduced up to 46% through postprocessing approaches, such as masking out less reliable regions, matching available echo timings and spatial resolution, avoiding the use of the nonconsistent magnitude contrast between scans in field estimation, and minimizing streaking artifacts. Abstract : QSM and R2 * reproducibility was studied in nonharmonized locally optimized data of 24 healthy traveling heads from three centers and two vendors. The cross‐site data for QSM and R2 * were highly correlated and reproducible. Cross‐site variability can be reduced via postprocessing, such as masking out less reliable regions, matching available echo timings and spatial resolution, avoiding the use of the nonconsistent magnitude contrast between scans in field estimation, and minimizing streaking artifacts.